2019
DOI: 10.1111/1471-0307.12653
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, microbiological, rheological, and sensory properties of yoghurts with new polysaccharide extracts from Lactarius volemus Fr. using three probiotics

Abstract: Polysaccharide extracts (0.05~0.15% w/w) from Lactarius volemus Fr. were used as growth factors and were incorporated into three different probiotic yoghurts. Yoghurts with polysaccharide extracts had a significantly improved water-retention capacity and reduced pH (P < 0.05). Polysaccharide extracts also significantly increased the viable count and essential amino acid content in the probiotic yoghurts (P < 0.05). The best sensory properties were achieved with the addition of 0.10% polysaccharide extracts. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The polyphenol-protein interaction which played an important role in serum separation depends on various factors including proteins and polyphenol nature, temperature, and presence of other bioactive compounds (Vital et al, 2015). However, an improvement of whey separation from the yogurt was reported by addition of Lactarius volemus Fr extract (Huang et al, 2020), Jerusalem artichoke powder (Guo et al, 2018), and mango (Narayana & Gupta, 2013) to the yogurt. Also, in a study by Amirdivani and Baba (2013) that used 2% of the Malaysian and Japanese green tea extracts in yogurt, syneresis was increased during the study, but the groups containing green tea extracts showed less syneresis than control group.…”
Section: Discussionmentioning
confidence: 99%
“…The polyphenol-protein interaction which played an important role in serum separation depends on various factors including proteins and polyphenol nature, temperature, and presence of other bioactive compounds (Vital et al, 2015). However, an improvement of whey separation from the yogurt was reported by addition of Lactarius volemus Fr extract (Huang et al, 2020), Jerusalem artichoke powder (Guo et al, 2018), and mango (Narayana & Gupta, 2013) to the yogurt. Also, in a study by Amirdivani and Baba (2013) that used 2% of the Malaysian and Japanese green tea extracts in yogurt, syneresis was increased during the study, but the groups containing green tea extracts showed less syneresis than control group.…”
Section: Discussionmentioning
confidence: 99%
“…The SL cultures containing ST (0.5 × 10 7 CFU mL −1 ) and LB 0.5 × 10 7 CFU mL −1 ), BCS cultures containing BCS (1 × 10 7 CFU mL −1 ), and BCS + SL cultures containing BCS (0.75 × 10 7 CFU mL −1 ) and SL (0.25 × 10 7 CFU mL −1 ). Yoghurts were prepared according to the protocol in our previous study (Huang et al ., 2020). During the period of fermentation of 0, 2, 4 and 6 h, yoghurts were collected for further measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that plant-derived polysaccharides have many potential biological activities, such as bacteriostasis; the promotion of wound healing; and antioxidation, antitumor, anti-inflammatory, and antiaging activities [ 37 ]. Polysaccharides contain many hydroxyls and polar groups, which can form hydrogen bonds with water molecules, leading to strong water retention characteristics [ 52 , 53 , 54 ]. Polysaccharides are one of the richest carbohydrate components in a lily, accounting for 10–36% of the bulb dry weight [ 55 , 56 , 57 ].…”
Section: Ingredients With Potential Application In Cosmetics In ...mentioning
confidence: 99%